The relations between helicobacter pylori infection and gastric emptying time - T. SARIÇAM,; E. VARDARELİ,; Y. AKGÜN,; N. E. VARDARELİ,; Y. KİŞİOĞLU,; E. GÜNEY,; E. ENTOK,; E. ERENOĞLU, (Turkish Journal of Gastroenterology, 2020)
-